Классификация и методы математического описания банковских рисков - Бидюк, П.И.; Басараб, А.В.; Гасанов, А.С. (Проблемы управления и информатики, 2009)
Представлено загальний опис фінансових ризиків, підходів до опису ризиків і математичних методів розрахунків та моделювання ризиків. Описано структуру ризику, надано рекомендації щодо зниження багатьох видів ризиків у різних ситуаціях та запобігання їм. Наведено математичні методи опису та розрахунків ризиків: розриви, простий VaR, ∆-γ-нормальний VaR, --нормальний VaR, метод історичного моделювання та метод Монте-Карло. Для кожного методу наведено приклади розрахунку та описано їх переваги і недоліки. Розглянуто такі види ризиків: операційний, ринковий, кредитний, діловий, ліквідності, юридичний. Для розрахунку ринкових ризиків використовуються декілька методів, найпростішим є розрахунок найбільшого збитку при заданому рівні довіри. Відсотковий ризик і ризик втрати ліквідності можуть бути обчислені з урахуванням розривів активів і пасивів. На значних історичних вибірках можна використовувати метод історичного моделювання. Найкращі результати досягаються за допомогою методу Монте-Карло, який базується на моделюванні процесів із заданими характеристиками. This article describes general introduction to financial risks and presents approaches to risks mathematical simulation. The risks structure, analysis approaches are described and recommendations for minimization of different kinds of risks in different situations are made. Mathematical methods for risks description and calculation are presented, such us: Gap, Value at Risks (VaR), Delta-Normal method of VaR calculation, Delta-Gamma-Normal method of VaR calculation, historical simulation, Monte-Carlo methods. The examples, advantages and disadvantages of each method and risk mitigation approaches are described. Most authors describe the following kinds of risks: operational, marketing, credit, business, liquid, low risks. Several methods can be used for calculation of market risks. Calculation of the biggest loss for standard confidential level. VaR is the simplest of them. Percentage and liquid risks can be calculated by creation of Gap function. The Historical simulation method can be used on the long historical samples. But the best results can be reached by using Monte-Carlo method, based on the simulation of the processes with standard parameters.